Cerebellar Loops with Motor Cortex and Prefrontal Cortex of a Nonhuman Primate - Kelly, Roberta M. (J Neurosci, 2003)
We used transneuronal transport of neurotropic viruses to examine the topographic organization of circuits linking the cerebellar cortex with the arm area of the primary motor cortex (M1) and with area 46 in dorsolateral prefrontal cortex of monkeys. Retrograde transneuronal transport of the CVS-11 (challenge virus strain 11) strain of rabies virus in cerebello-thalamocortical pathways revealed that the arm area of M1 receives input from Purkinje cells located primarily in lobules IV-VI of the cerebellar cortex. In contrast, transneuronal transport of rabies from area 46 revealed that it receives input from Purkinje cells located primarily in Crus II of the ansiform lobule. Thus, both M1 and area 46 are the targets of output from the cerebellar cortex. However, the output to each area of the cerebral cortex originates from Purkinje cells in different regions of the cerebellar cortex. Anterograde transneuronal transport of the H129 strain of herpes simplex virus type 1 (HSV1) revealed that neurons in the arm area of M1 project via the pons to granule cells primarily in lobules IV-VI, whereas neurons in area 46 project to granule cells primarily in Crus II. Together, the findings from rabies and HSV1 experiments indicate that the regions of the cerebellar cortex that receive input from M1 are the same as those that project to M1. Similarly, the regions of the cerebellar cortex that receive input from area 46 are the same as those that project to area 46. Thus, our observations suggest that multiple closed-loop circuits represent a fundamental architectural feature of cerebrocerebellar interactions.